2019
DOI: 10.5564/pmas.v59i3.1247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic comparison of Altai and Gobi argali sheep (Ovis ammon) populations using mitochondrial and microsatellite markers: Implication on conservation

Abstract: Argali sheep is an ungulate, which inhabits the north, west, south and central regions of Mongolia. There are two major populations (Altai and Gobi) in Mongolia, but their taxonomic classification as subspecies is often disputed among researchers. Furthermore, there is no recent study about the population genetic structure of argali sheep in Mongolia. In the present study, we have investigated genetic diversity and difference between Altai and Gobi argali populations using mitochondrial control region hyper va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In the study of the mitochondrial control region and 14 microsatellite loci of argali from the Altai Mountains, Hangay Mountains and eastern Gobi Desert, Feng et al [25] indicated genetic differentiation among these groups. Using mitochondrial control region hypervariable segment sequence (598 bp) and three microsatellite markers Delgerzul et al [27] stated that the genetic difference between Altai and Gobi populations was at the subspecies level. The results of our work agree with the study of Tserenbataa et al [24], where using the ND5 gene of mitochondrial DNA, the authors revealed low genetic differentiation and a high level of gene flow among populations and concluded that O. a. ammon and O. a. darwini should be considered a single subspecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of the mitochondrial control region and 14 microsatellite loci of argali from the Altai Mountains, Hangay Mountains and eastern Gobi Desert, Feng et al [25] indicated genetic differentiation among these groups. Using mitochondrial control region hypervariable segment sequence (598 bp) and three microsatellite markers Delgerzul et al [27] stated that the genetic difference between Altai and Gobi populations was at the subspecies level. The results of our work agree with the study of Tserenbataa et al [24], where using the ND5 gene of mitochondrial DNA, the authors revealed low genetic differentiation and a high level of gene flow among populations and concluded that O. a. ammon and O. a. darwini should be considered a single subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Different mitochondrial and nuclear DNA markers were used to clarify phylogenetic relationships in ungulate species [17][18][19][20][21][22][23]. Until now, molecular genetic studies of argali have been carried out using mitochondrial DNA [23,24] and microsatellites [25][26][27].…”
Section: Introductionmentioning
confidence: 99%